Using XSLT on bioinformatic XML data when data changes frequently. - Bruhn, Russel
For the biologist, the bioinformatic analysis of genes requires the compilation of tables of gene characteristics. To do this, data is often taken manually out of databases in an ad hoc fashion. Different databases (TIGR, MIPS, BLAIR and NCBI, for example, give different outputs in different formats. We would like to be able to extract information from the databases in a common, structured file format in a way that allows for easy rearranging and processing of the data.